Analisis Penerapan Metode Tafsir Al-Maraghi terhadap Kemampuan Interpretasi Al-Qur'an - Ega Maturrochman; Eli Masnawati (LP3M IAI Al Urwatul Wutsqo Jombang, 2024)
This research examines the application of the Al-Maraghi exegesis method and its impact on the Al-Qur'an interpretation abilities of Santri at the Kalimasada Jombang Islamic Boarding School. Using a qualitative approach with a case study design, this research involved in-depth interviews with caregivers, Ustadz, and students, class observations, and document analysis. The research results show that the Al-Maraghi method has significant potential in increasing contextual understanding and the relevance of the Al-Qur'an to contemporary issues. However, implementation is still limited due to a lack of lecturer understanding, limited resources, and resistance to change. Variations in the adoption and effectiveness of these methods across institutions are influenced by factors such as institutional support and access to resources. Students exposed to this method report an increased ability to understand and apply the message of the Qur'an in a modern context. This research underlines the importance of curriculum reform, developing lecturer capacity, and providing contextual learning materials. These findings contribute to the discourse on Islamic education reform and its role in shaping an understanding of Islam that is relevant in the modern era. Research implications include the need to revitalize the curriculum, integrate contemporary approaches in Al-Qur'an exegesis, and develop more effective pedagogical strategies in teaching contextual exegesis methods.